2016
DOI: 10.21522/tijar.2014.03.01.art013
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Phones among Undergraduate Students-a Case in Ghana

Abstract: The response to the development and growth of mobile phones in Africa has introduced new ideas in education, business, health, and banking needs of a country. Ghana has become a great place for mobile technology implementation to thrive as there are enough users to support the relevant technologies. In fact, the latest industry statistics released by the National Communications Authority state that, out of a population of 24.97 million, there are approximately 24.4 million subscribers on at least one of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The survey research approach is considered as the preferred choice by researchers for collecting original data from a large population. The Survey methods are widely used and acknowledged research approach [14]. Moreover, the concept of collecting data from a small sample of population to be an accurate representation of a larger sample has also become a common practice among researchers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey research approach is considered as the preferred choice by researchers for collecting original data from a large population. The Survey methods are widely used and acknowledged research approach [14]. Moreover, the concept of collecting data from a small sample of population to be an accurate representation of a larger sample has also become a common practice among researchers.…”
Section: Methodsmentioning
confidence: 99%
“…The research results by Quist and Quarshie [14] in Ghana, indicated that college students use mobile technologies for various activities which include; listening to music, playing games, watching movies, social networking, work-related research, educational research, religious programmes, personal finance, current events and making & receiving calls.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the behavioural addiction of student's use of cell phones remains a serious challenge [19]. Even though studies have been conducted on the use of mobile phones among university students in Ghana [20,21], the specific behaviours students exhibit in the use of the cell phones and the counselling implications were not key in their investigations. The purpose of the study, therefore, is to assess the kinds of behaviours regular undergraduate students exhibit in the use of cell phones on campus.…”
Section: Introductionmentioning
confidence: 99%